An Experimentation of Chemical and Mechanical Behaviour of Epoxy-Sisal Reinforced Composites. Issue 3 (March 2017) - Yuvaraj, G.; Kumar, Hemanth; Saravanan, G.
In this work the variation of mechanical properties like tensile, impact and chemical resistance properties of randomly oriented sisal/glass fibre reinforced hybrid composites with different fibre ratios (50:50, 45:55, 40:60, 30:70) was studied. Hand lay up method is used for making the composites with epoxy resin. The result shows that increase in chemical, impact properties of composites with increase in fibre loading. Also it was observed that significant improvement in tensile properties of hybrid composites by alkali treatment.